급지별 법원 규모에 따른 공간기능 구성과 동선계획 - 오재훈(Jae-Hun Oh); 이강희(Kang-Hee Lee) (KIEAE Journal, 2024)
Purpose: This study aims to investigate the layout, floor plans, and spatial planning of domestic courthouses to propose design solutions that address changing spatial demands and functions, including circulation paths and spatial function composition. Method: This study focused on district courts, branch courts, and municipal courts, selecting two from each region for investigation. The six selected courthouses were compared and analyzed in terms of size based on regional classification, as well as spatial composition and flow of circulation according to their local characteristics. Data on spatial functions and circulation flow were primarily gathered from publicly available resources, such as the courthouses' websites, layout plans, and circulation maps. The internal layout plans were analyzed by examining the locations of departments and circulation paths using both online resources and field investigations. User circulation patterns were assessed by referencing organizational guides and layout plans, as well as through staff interviews to understand both employee and citizen movement. Field investigations allowed for the analysis of the spatial locations of departments and circulation flow, focusing on zoning for both citizens and staff. Result: This paper can serve as foundational material for developing spatial compositions and circulation plans that respond to the spatial function needs of citizens using courthouses, particularly as the changing times and interests (such as wealth management, auctions, self-registration, and self-representation) have led to an increase in public access and the rise of self-representing litigants. It also outlines design concepts that future courthouse buildings should aim to achieve. KCI Citation Count: 0